2010
DOI: 10.1002/dvdy.22230
|View full text |Cite
|
Sign up to set email alerts
|

Non‐apoptotic cell death in Caenorhabditis elegans

Abstract: The simple nematode worm Caenorhabditis elegans has been instrumental in deciphering the molecular mechanisms underlying apoptosis. Beyond apoptosis, several paradigms of non-apoptotic cell death, either genetically or extrinsically triggered, have also been described in C. elegans. Remarkably, non-apoptotic cell death in worms and pathological cell death in humans share numerous key features and mechanistic aspects. Such commonalities suggest that similarly to apoptosis, non-apoptotic cell death mechanisms ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 133 publications
0
23
0
Order By: Relevance
“…Necrosis is most frequently observed during cell injury, and is closely associated with diseases such as stroke, neurodegeneration, chronic inflammation, and cancer [3–7]. Although necrosis was historically considered an uncontrolled cell death event caused by acute damage, recent discoveries made in multiple organisms demonstrated that in addition to injury-induced necrosis, cells possess genetic pathways that specifically trigger necrosis in response to extracellular or intracellular stimuli (reviewed in [811]). For instance, tumor necrosis factor (TNF) induces a necrosis pathway executed through Ser/Thr kinases [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Necrosis is most frequently observed during cell injury, and is closely associated with diseases such as stroke, neurodegeneration, chronic inflammation, and cancer [3–7]. Although necrosis was historically considered an uncontrolled cell death event caused by acute damage, recent discoveries made in multiple organisms demonstrated that in addition to injury-induced necrosis, cells possess genetic pathways that specifically trigger necrosis in response to extracellular or intracellular stimuli (reviewed in [811]). For instance, tumor necrosis factor (TNF) induces a necrosis pathway executed through Ser/Thr kinases [10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, hyperexcitation of neurons or glial cells induced by the massive release of neurotransmitters or constitutively active ion channels cause excitotoxic necrosis [7,12,13]. Unlike apoptosis, which relies on caspase-mediated death-triggering mechanisms, known necrosis-triggering pathways appear to be independent of caspase-activities (reviewed in [8,14]). On the other hand, like apoptotic cells, in many cases necrotic cells have been observed to be engulfed by phagocytes [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells in C. elegans can also die through non-apoptotic means, including various types of non-apoptotic programmed cell death and necrotic-like death (reviewed in [42]). Intriguingly, the 'apoptotic' engulfment machinery can recognize and clear most if not all of types of cell corpses, irrespective of the cause of death.…”
Section: Clearance Of Non-apoptotic Corpses and Of Sick Cellsmentioning
confidence: 99%
“…Genetic perturbations and/or various treatments can also lead to various forms of nonapoptotic cell death in C. elegans (pathological cell death). Since this type of cell death does not occur during normal C. elegans development and since it has recently been reviewed (Vlachos and Tavernarakis 2010;Kinet and Shaham 2014), it will not be covered here.…”
mentioning
confidence: 99%